Adelie penguins -- photograph - Seale, Linda N. (2004)
Adelie penguins on the Yalour Islands, Antarctic Peninsula. The bird on the left is stealing a pebble to add to its own nest. The smaller bird with brown feathers is a half-grown chick. January 2004